Case report: Acute kidney injury as the initial manifestation of chronic lymphocytic leukemia/small lymphocytic lymphoma - Bender, Sascha T.; Zeremski, Vanja; Wiech, Thorsten; Mertens, Peter R.; Gross, Christian (Frontiers in Medicine, 2023)
Chronic lymphocytic leukemia (CLL) is a lymphoproliferative disorder often diagnosed after incidental finding of leukocytosis. Renal involvement is usually clinically silent. Symptomatic renal impairment due to CLL/small lymphocytic lymphoma (SLL) cell infiltration in the kidney tissue is uncommon, and acute kidney injury (AKI) as a presenting feature is rare. In this case report, we describe the case of a patient with AKI caused by CLL/SLL infiltration as a presenting feature. Our report highlights the possibility of kidney injury as the first evident symptom of CLL/SLL. Kidney biopsy is the mainstay in these cases in order to establish a diagnosis. Treatment with zanubrutinib resulted in improved kidney function.